The Implementation of Meaningful Participation in Lawmaking: A Comparative Study and Its Implications for Indonesia - Sa’adati; Muhammad Yopan (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to analyze the implementation of meaningful participation in lawmaking in Indonesia, compare it with practices in South Africa and Kenya, and examine its implications for strengthening legislative governance in Indonesia. This study employs a qualitative approach enriched with comparative analysis and public policy analysis. The data used consist of secondary data, including legislation, Constitutional Court decisions, reports, and articles relevant to public participation practices in the comparison countries. The results of the study indicate that although Indonesia has a legal foundation that recognizes public participation, its implementation remains procedural and does not yet meet the indicators of meaningful participation, such as access to information, representation, substantive influence, deliberation, and accountability. A comparative study with South Africa and Kenya shows that similar challenges exist, even though both countries have normative reinforcement at the constitutional level. The main issues lie in implementation, particularly limited access, the dominance of elite groups, weak feedback mechanisms, and minimal public influence on policy substance. This study concludes that strengthening meaningful participation in Indonesia requires improvements in institutional design, stronger accountability mechanisms, and a paradigm shift from procedural participation to substantive participation.